CRIMINAL LEGAL RESPONSIBILITY FOR THE USE OF NURSING PERSONNEL IN ANESTHESIA SERVICES: A LEGAL ANALYSIS FROM THE PERSPECTIVE OF LAW NUMBER 17 OF 2023 CONCERNING HEALTH - Bahrun Sihotang; Moh. Lubsi Tuqo Romadhan (Journal of International Islamic Law, Human Right and Public Policy, 2026)
The use of nursing staff in anesthesia services has become a common practice in various Indonesian healthcare facilities. However, the arrangement of authority between "Nurse Anesthesiologist" and "Anesthesia Administrator" creates legal ambiguity that has the potential to lead to criminal liability in the event of malpractice. The purpose of this study is to analyze the construction of criminal liability for nurses and healthcare institutions in anesthesia services based on Law No. 17/2023 and to examine the limits of clinical authority that form the basis of such liability. The research method used is a normative juridical method with a statutory and conceptual approach. Analysis was conducted on related sectoral regulations and court decisions. The results of the study show that Law No. 17/2023 provides a clear legal basis regarding the obligations, authority, and criminal sanctions for nursing staff in anesthesia services. Negligence in anesthesia practice is a form of legal error that can give rise to criminal liability. Criminal liability is personal in nature, but under certain conditions it can be extended to healthcare institutions. The integration between Law No. 17/2023 emphasizes the importance of professional, safe and effective health service management obey the law. The implications of the research results are that Law No. 17/2023 have provided a strong legal basis in regulating the practice of nursing personnel in anesthesia services, so that any negligence committed must be in accordance with the established authority. Negligence in anesthesia practice is not only seen as a professional error, but also as an unlawful act that can give rise to criminal liability both individually and under certain conditions on a procedural basis.